Heat shock protein 70 and tumor‐infiltrating NK cells as prognostic indicators for patients with squamous cell carcinoma of the head and neck after radiochemotherapy: A multicentre retrospective study of the German Cancer Consortium Radiation Oncology Group (DKTK‐ROG). Issue 9 (23rd December 2017) - Stangl, Stefan; Tontcheva, Nikoletta; Sievert, Wolfgang; Shevtsov, Maxim; Niu, Minli; Schmid, Thomas E.; Pigorsch, Steffi; Combs, Stephanie E.; Haller, Bernhard; Balermpas, Panagiotis; Rödel, Franz; Rödel, Claus; et al.
Abstract : Tumor cells frequently overexpress heat shock protein 70 (Hsp70) and present it on their cell surface, where it can be recognized by pre‐activated NK cells. In our retrospective study the expression of Hsp70 was determined in relation to tumor‐infiltrating CD56 + NK cells in formalin‐fixed paraffin embedded (FFPE) tumor specimens of patients with SCCHN ( N = 145) as potential indicators for survival and disease recurrence. All patients received radical surgery and postoperative cisplatin‐based radiochemotherapy (RCT). In general, Hsp70 expression was stronger, but with variable intensities, in tumor compared to normal tissues. Patients with high Hsp70 expressing tumors (scores 3–4) showed significantly decreased overall survival (OS; p = 0.008), local progression‐free survival (LPFS; p = 0.034) and distant metastases‐free survival (DMFS; p = 0.044), compared to those with low Hsp70 expression (scores 0–2), which remained significant after adjustment for relevant prognostic variables. The adverse prognostic value of a high Hsp70 expression for OS was also observed in patient cohorts with p16‐ ( p = 0.001), p53‐ ( p = 0.0003) and HPV16 DNA‐negative ( p = 0.001) tumors. The absence or low numbers of tumor‐infiltrating CD56 + NK cells also correlated with significantly decreased OS ( p = 0.0001), LPFS ( p = 0.0009) and DMFS ( p = 0.0001). A high Hsp70 expression and low numbers of tumor‐infiltrating NK cells have the highest negative predictive value ( p = 0.00004). In summary, a strong Hsp70 expression and low numbers of tumor‐infiltrating NK cells correlate with unfavorable outcome following surgery and RCT in patients with SCCHN, and thus serve as negative prognostic markers. Abstract : What's new? It's difficult to predict how a patient with squamous‐cell carcinoma of the head and neck (SCCHN) will respond to treatment, because every tumor is different. In this study, the authors identified two pre‐treatment measures that were associated with poor prognosis following surgery and RCT: high levels of staining for a protein called Hsp70 in tumor cells, and low numbers of tumor‐infiltrating NK lymphocytes. These measures may thus serve as useful prognostic biomarkers for predicting the response of SCCHN to therapy.